Impact of immigration status on health behaviors and perceptions in cancer survivors. (21st March 2019) - Liu, Sophia Y.; Lu, Lin; Pringle, Dan; Mahler, Mary; Niu, Chongya; Charow, Rebecca; Tiessen, Kyoko; Lam, Christine; Halytskyy, Oleksandr; Naik, Hiten; Hon, Henrique; Irwin, Margaret; et al.
Abstract: Background: Health behaviors including smoking cessation, physical activity (PA), and alcohol moderation are key aspects of cancer survivorship. Immigrants may have unique survivorship needs. We evaluated whether immigrant cancer survivors had health behaviors and perceptions that were distinct from native‐born cancer survivors. Methods: Adult cancer patients from Princess Margaret Cancer Centre were surveyed on their smoking, PA, and alcohol habits and perceptions of the effects of these behaviors on quality of life (QoL), 5‐year survival, and fatigue. Multivariable models evaluated the association of immigration status and region‐of‐origin on behaviors and perceptions. Results: Of the 784 patients, 39% self‐identified as immigrants. Median time of survey was 24 months after histological diagnosis. At baseline, immigrants had trends toward not meeting Canadian PA guidelines or being ever‐drinkers; patients from non‐Western countries were less likely to smoke (aORcurrent  = 0.46, aORex‐smoker  = 0.47, P  = 0.02), drink alcohol (aORcurrent  = 0.22, aORex‐drinker  = 0.52, P  < 0.001), or meet PA guidelines (aOR = 0.44, P  = 0.006). Among immigrants, remote immigrants (migrated ≥40 years ago) were more likely to be consuming alcohol at diagnosis (aOR = 5.70, P  < 0.001) compared to recent immigrants. Compared to nonimmigrants, immigrants were less likely to perceive smoking as harmful on QoL (aOR = 0.58, P  = 0.008) and survival (aOR = 0.56, P  = 0.002), and less likely to perceive that PA improved fatigue (aOR = 0.62, P  = 0.04) and survival (aOR = 0.64, P  = 0.08). Conclusions: Immigrants had different patterns of health behaviors than nonimmigrants. Immigrants were less likely to perceive continued smoking as harmful and were less likely to be aware of PA benefits. Culturally tailored counselling may be required for immigrants who smoke or are physically sedentary at diagnosis. Abstract : Immigrant cancer survivors had different patterns of health behaviors than nonimmigrants. Culturally tailored counselling may be required for immigrants who smoke or are physically sedentary at diagnosis